Morphological differences in the Galaxias maculatus (Jenyns, 1842) population an osmeriform fish from southern, Argentina - Ferriz, Ricardo Alberto (2001)
Samples of the puyen Galaxias maculatus (Galaxiidae) from four localities at the Limay river basin were subjected to Principal Component Analysis of morphometric traits. The analysis portrayed different body characteristics among samples from sections of the river with different physical and water chemistry traits. Samples from the Ramos Mexia dam and downstream, are composed of slender individuals of varied sizes, living under slow curren to vegetated muddy bottoms.